Decarbonization and liberalization in the power sector: international perspectives - Bassam Fattouh; Malcolm Keay; Rahmatallah Poudineh; David Robinson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2018)
Oxford Energy Forum 104 (February 2016) looked at the transformation under way in the electricity sector, driven by technological developments and policies on decarbonization. It focused mainly on OECD (Organisation for Economic Co-operation and Development) countries, and on Europe in particular, where there are major challenges, ranging from the practical issues associated with the integration of the new intermittent renewable sources to the wider policy question of whether there is a fundamental conflict between two objectives – decarbonization and liberalization – to which these countries are committed. This issue of the Forum explores related issues, but on a wider canvas – countries across the world, with a diverse range of approaches, many outside the OECD.
Keywords: 330